Emerging and Novel Functions of Complement Protein C1q - Kouser, Lubna; Madhukaran, Shanmuga Priyaa; Shastri, Abhishek; Saraon, Anuvinder; Ferluga, Janez; Al-Mozaini, Maha; Kishore, Uday (Frontiers in Immunology, 2015)
Complement protein C1q, the recognition subcomponent of the classical pathway, performs a diverse range of complement and non-complement functions. It can bind various ligands derived from self, non-self and altered-self and modulate the functions of immune and non-immune cells including dendritic cells and microglia. C1q involvement in the clearance of apoptotic cells and subsequent B cell tolerance is more established now. Recent evidence appears to suggest that C1q plays an important role in pregnancy where its deficiency and dysregulation can have adverse effects, leading to preeclampsia, missed abortion, miscarriage or spontaneous loss and various infections. C1q is also produced locally in the Central Nervous System, and has a protective role against pathogens and possible inflammatory functions while interacting with aggregated proteins leading to neurodegenerative diseases. C1q role in synaptic pruning, and thus CNS development, anti-cancer effects as an immune surveillance molecule, and possibly in ageing are areas of extensive research.